International environmental law : fairness, effectiveness, and world order - Louka, Elli (Cambridge University Press, 2006)
This book analyzes the law and policy for the management of global common resources. As competing demands on the global commons are increasing, the protection of environment and the pursuit of growth give rise to all sorts of conflicts. It also analyzes issues in the protection of the global commons from a fairness, effectiveness and world order perspective. The author examines whether policymaking and trends point to a fair allocation of global common resources that is effective in protecting the environment and the pursuit of sustainable development. The author looks at the cost-effectiveness of international environmental law and applies theories of national environmental law to international environmental problems. Chapters include analysis on areas such as marine pollution, air pollution, fisheries management, transboundary water resources, biodiversity, hazardous and radioactive waste management, state responsibility and liability.